Estudo da Helmintofauna em Cães domésticos (Canis lupus familiaris) no entorno do Jardim Botânico da Universidade Federal de Juiz de Fora, Minas Gerais, Brasil. - Nascimento, André Luiz (Universidade Federal de Juiz de Fora (UFJF), 2022)
The growth of human populations and the consequent increase in domestic animals around protected areas increase the opportunities for disease transmission. Wild Canids are closely related to domestic dogs and are susceptible to many of their disease agents. These pathogens cause multisystem infections, mortality, low birth rates and therefore pose serious threats to the conservation of wild Canids. The objective of this study was to evaluate the environmental contamination around the Botanical Garden of the Federal University of Juiz de Fora, and the presence of gastrointestinal parasites in feces samples from dogs in the region. For this, 45 stool samples were collected and sent to the laboratory to be analyzed. Of the 45 samples, 20 (42.2%) were positive for eggs of gastrointestinal parasites, with 45% (9/20) being contaminated by Ancylostoma caninum. In all, eggs of Ancylostoma caninum (n=9; 45.0%), Ascaridida (n=7; 35.0%), Uncinaria stenocephala (n=2; 10.0%), Enterobius vermicularis (n=1 5.0%) and Physaloptera praeputialis (n=1; 5.0%). This result shows us a great potential for transmission between dogs in the region and the Maned Wolf that reside in the Botanical Garden, with the exception of Enterobius vermicularis, all parasites recorded also occur in the Maned Wolf, in addition to being zoonotic, such as, for example , the cutaneous larva migrans, caused by Ancylostoma caninum and Uncinaria stenocephala. The results of this study support the need for measures that reduce the contamination between dogs in the region and animals that reside in the Botanical Garden. O crescimento das populações humanas e o consequente aumento de animais domésticos em torno de áreas protegidas aumentam as oportunidades para a transmissão de doenças. Os canídeos selvagens estão intimamente relacionados com os cães domésticos e são suscetíveis a muitos dos seus agentes de doenças. Esses patógenos causam infecções multissistêmicas, mortalidade, baixas taxas de natalidade e, portanto, representam graves ameaças para a ...